Differences in perception of safety in driving environment according to shared PMD user experience through multi-criteria analysis. Issue 2 (February 2023) - Cho, Min Kyoung; Kang, Min Gu; Kwon, Youngsang
Abstract: A shared personal mobility device (PMD) is a transportation model that rents personal transportation devices, such as bicycles and kickboards, through a sharing platform. The use of shared PMD has increased, but related complaints and traffic accidents are doubling with it every year. This study applied an analytic network process (ANP) methodology for the multi-criteria analysis. A survey including normal citizens was conducted to evaluate the importance of safety regarding shared PMD experience. The evaluation factors differ according to the experience of using the shared PMD device, although 'driving continuity' and 'separation of sidewalks and roadways' were the most important. PMD users gave greater priority to 'removal of the road gap', 'traffic safety signs', 'dedicated parking area' and 'management of obstacles' compared to non-users. On the other hand, for non-PMD users, 'bicycle lane width', 'strengthening enforcement', and 'user safety education' were more important. The results showed that importance differed depending on the participant's experience of using a shared PMD or the lack of it. In the case of users, factors that have a direct effect on driving were prioritised, and in the case of non-users, auxiliary operations and management, such as crackdowns and education, were prioritised.